Oligodendrogenesis and Myelin Formation in the Forebrain Require Platelet-derived Growth Factor Receptor-alpha. (1st June 2020) - Hamashima, Takeru; Ishii, Yoko; Nguyen, Linh Quang; Okuno, Noriko; Sang, Yang; Matsushima, Takako; Kurashige, Yoichi; Takebayashi, Hirohide; Mori, Hisashi; Fujimori, Toshihiko; Yamamoto, Seiji; Sasahara, Masakiyo
Highlights: Differentiation of oligodendroglial-lineage was largely suppressed in embryo. Decrease of population expansion of oligodendroglial-lineage was mild in embryo. Oligodendroglial-lineage cells mostly died after birth. The neonatal brains were severely hypomyelinated. Aberrant overgrowth of blood vessels appeared, and the neuronal axons degenerated. Abstract: The platelet-derived growth factor receptor-α (PDGFRα) principally mediates growth factor signals in oligodendroglial progenitors and is involved in oligodendrogenesis and myelinogenesis in the developing spinal cord. However, the role of PDGFRα in the developing forebrain remains relatively unknown. We established a conditional knockout mouse for the Pdgfra gene (N-PRα-KO) using a Nestin promoter/enhancer-driven Cre recombinase and examined forebrain development. The expression of PDGFRα was efficiently suppressed in the Olig2 + cells in N-PRα-KO mice. In these mice, Olig2 + cells were slightly decreased during embryonic periods. The decrease was particularly striking during the postnatal period. The commitment of Pdgfra -inactivated Olig2 + cells to Sox10 + oligodendroglial-lineage was largely suppressed. Surviving Olig2 + cells and Sox10 + cells were distributed widely in the N-PRα-KO mouse brain, similarly to those in control mice until the early neonatal period. After that, these cells were drastically depleted in the forebrain during the second postnatal week. The brains of N-PRα-KO mice were severely hypomyelinated, and these mice died on approximately P17 with motor disturbances. Disturbed axonal fibers and extensively aberrant vascular formations appeared in the postnatal N-PRα-KO mouse brains. After the defective PDGFRα signal in the forebrain, these phenotypes were clearly different from those in the spinal cord that showed defective populations expansion and migration of oligodendroglial lineage and premature myelination, as previously described. In contrast, areas of severe hypomyelination were common to both anatomical sites. PDGFRα was critically involved in the myelination of the forebrain and may differently regulate oligodendroglial lineage between the forebrain and spinal cord.